+0  
 
0
103
3
avatar+193 

Find the constant $t$ such that

\[(5x^2 - 6x + 7)(4x^2 +tx + 10) = 20x^4 -54x^3 +114x^2 -102x +70.\]

 Feb 14, 2021
 #1
avatar+32817 
+1

5x2 * tx + -6x * 4x2 = -54 x^3

5t - 24 = -54

5t = -30

t =-6

 Feb 14, 2021
 #2
avatar+544 
+1

(5x2 - 6x + 7)(4x2 + tx + 10)

= 20x4 + 5tx3 + 50 x2 - 24x3 - 6tx2 - 60x + 28x2 + 7tx + 70
 

= 20x4 + (5t - 24)x3 + (78 - 6t)x2 + (7t - 60)x + 70

-54x3 = (5t - 24)x3
         
t = -6
 

114x2 = (78 - 6t)x2

        t = -6

 

-102x = (7t - 60)x

        t = -6

 Feb 14, 2021
 #3
avatar+113739 
0

Don't you two realize that this child is blatently cheating.  She is not trying to learn anything.

By answering all her questions (often in full) you are condoning her behaviour.

 Feb 14, 2021

16 Online Users

avatar
avatar